THE LEGISLATIVE RATIO AND EXISTENCE OF THE MPR BEFORE AND AFTER THE AMENDMENT TO THE 1945 CONSTITUTION - Batjo, Hamdan Saleh (Universitas prof. Dr. Moestopo (Beragama), 2025)
The People's Consultative Assembly (MPR) has historically occupied a central role within Indonesia's constitutional framework. Before the amendments to the 1945 Constitution, the MPR functioned as the highest state institution, exercising full Sovereignty of the people and holding constitutional supremacy. However, following the 1998 Reform Era and through four stages of constitutional amendments (1999–2002), the MPR's status fundamentally shifted into a high state organ equal to other constitutional bodies within the framework of checks and balances. This study analyzes the ratio legis of the MPR's establishment and its existence before and after the constitutional amendments. The research method is normative legal research, supported by historical and conceptual approaches. The findings reveal that although the MPR's Authority has been significantly reduced, it plays strategic roles, including amending and enacting the Constitution, inaugurating the President and Vice President, and serving as a forum for national representation. The post-amendment existence of the MPR reflects an adaptation to constitutional democracy while also sparking debates on its institutional repositioning. Strengthening the MPR's role remains essential to ensuring political and constitutional stability in Indonesia.